Nutrient composition and health benefits - Baye, Kaleab (International Food Policy Research Institute, 2018)
This chapter looks at the physical and chemical characteristics of teff and its nutrient composition. The use of teff and teff-based products for human nutrition in Ethiopia are described, along with the food-processing challenges impeding teff’s worldwide consumption. Recent research advances to solve these challenges are discussed. Finally, the potential health benefits that could be associated with higher consumption of teff are highlighted.